Aktualisasi Metode Guru Aqidah Akhlak dalam Meningkatkan Motivasi Belajar Siswa Kelas VIII - Alfiyan Nala; Mohammad Saat Ibnu Waqfin; Muhammad Aliyul Wafa (YASIN, 2026)
Although teaching methods have been widely studied in the context of Islamic religious education, research specifically addressing the actualization of Aqidah Akhlak teachers’ methods in improving students’ learning motivation at the madrasah tsanawiyah level remains limited. This study aimed to describe and analyze the actualization of Aqidah Akhlak teachers’ methods in improving the learning motivation of Grade VIII students at MTs Al Ihsan Kalikejambon, Jombang. The study employed a qualitative approach with a descriptive design involving Aqidah Akhlak teachers, Grade VIII students, the madrasah principal, and the vice principal for curriculum as informants selected through purposive sampling. Data were collected through in-depth interviews, direct observation, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The findings showed that teachers actualized a combination of varied lecture methods, question-and-answer sessions, feedback, exemplary conduct (uswah), and habituation supported by Qur’anic reading and writing (BTQ), tahfiz, and tahsin programs. The application of these methods created more interactive and communicative learning and increased students’ engagement, enthusiasm, and learning motivation. Their implementation was supported by teacher competence, supportive madrasah policies, adequate facilities, and religious habituation programs, whereas limited instructional time, diverse student characteristics, and less conducive classroom conditions were inhibiting factors. These findings affirm that the consistent and student-oriented actualization of teaching methods plays an important role in maintaining learning motivation in the Aqidah Akhlak subject. This study provides practical implications for teachers and madrasah policymakers to strengthen feedback- and habituation-based methods and opens opportunities for further research with a broader sample and a mixed-methods design.